2006
DOI: 10.1111/j.1440-1754.2006.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Health service utilisation of a regional cohort of very preterm infants over the first 2 years of life

Abstract: Very preterm infants had higher rates of hospital admissions and visits than term infants unrelated to neurodevelopmental outcome at 2 years of age. These findings highlight that very preterm birth is associated with ongoing health morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 25 publications
5
37
1
Order By: Relevance
“…Various studies across the world have tried to ascertain the neonatal risk factor for post NICU discharge hospital re-admission [1][2][3][8][9][10][11][12][13]. Ambalavanan, et al in their recent publication using classification and regression tree analysis concluded that neonates who spent > 120 days during their NICU admission for pulmonary reasons had a 66% re-hospitalization rate compared to 42% without such stay [3].…”
Section: Risk Factors For Hospital Re-admissionmentioning
confidence: 99%
See 4 more Smart Citations
“…Various studies across the world have tried to ascertain the neonatal risk factor for post NICU discharge hospital re-admission [1][2][3][8][9][10][11][12][13]. Ambalavanan, et al in their recent publication using classification and regression tree analysis concluded that neonates who spent > 120 days during their NICU admission for pulmonary reasons had a 66% re-hospitalization rate compared to 42% without such stay [3].…”
Section: Risk Factors For Hospital Re-admissionmentioning
confidence: 99%
“…Previous Australasian data describes a readmission rate of 42% for VLBW infants [9] and 55% for very preterm infants [2].…”
Section: Features Of In-patientsmentioning
confidence: 99%
See 3 more Smart Citations